School-Related Irrational Beliefs as Predictor of Academic Motivation among Secondary School Learners - Boitumelo Molebogeng Diale; Vera Victor-Aigbodion (Studies in Learning and Teaching, 2022)
Learners' thoughts are important for academic motivation and learning in secondary schools. Specifically, this study aims to determine the extent to which school-related irrational beliefs influence academic motivation among secondary school students. Using a multi-stage random sampling technique, 740 secondary school students of both genders were selected as a sample: 303 boys and 437 girls. The Irrational Beliefs Inventory (IBI) and the Academic Motivation Scale (AMS) were used for data collection. In order to answer research questions, mean scores, standard deviations, and Pearson product moment correlation analysis were used while the hypotheses were tested using regression analysis at 0.05 level of significance. A statistically significant relationship was found between irrational beliefs and academic motivation among secondary school learners. A key recommendation of the study is that secondary school psychologists should teach learners on the adverse impact of irrational beliefs.